Critical Study of Amina Wadud's Thought in the Issue of Inheritance - Fauzan Zenrif; Syabbul Bachri (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
This study aims to examine the main arguments presented by Amina Wadud on inheritance in her book